Incomplete penetrance of a novel SDHD variation causing familial head and neck paraganglioma. (5th May 2021) - Koenighofer, Martin; Parzefall, Thomas; Frohne, Alexandra; Frei, Elisabeth; Schoefer, Christian; Laccone, Franco; Feil, Patricia; Frei, Klemens; Lucas, Trevor
Abstract: Objective: Identification of variations in tumour suppressor genes encoding the tetrameric succinate dehydrogenase (SDHx) mitochondrial enzyme complex may lead to personalised therapeutic concepts for the orphan disease, familial paraganglioma (PGL) type 1‐5. We undertook to determine the causative variation in a family suffering from idiopathic early‐onset (22 ± 2 years) head and neck PGL by PCR and Sanger sequencing. Design: Prospective genetic study. Setting: Tertiary Referral Otolaryngology Centre. Participants: Twelve family members. Main outcome measures: Main outcomes were clinical analysis and SDH genotyping Results and Conclusions: A novel heterozygous c.298delA frameshift variation in exon 3 of SDH subunit D (SDHD) was associated with a paternal transmission pattern of PGL in affected family members available to the study. Family history over five generations in adulthood indicated a variable penetrance for PGL inheritance in older generations. The c.298delA variant would cause translation of a 34‐residue C‐terminus distal to lysine residue 99 in the predicted transmembrane domain II of the full‐length sequence p.(Thr100LeufsTer35) and would affect the translation products of all protein‐coding SDHD isoforms containing transmembrane topologies required for positional integration in the inner mitochondrial membrane and complex formation. These results underly the importance of genetic screening for PGL also in cases of unclear inheritance, and variation carriers should benefit from screening and lifelong follow‐up.